GABA and GLP-1 receptor agonist combination therapy modifies diabetes and Langerhans islet cytoarchitecture in a rat model of Wolfram syndrome - Toomas Jagomäe; Sandra Velling; Tessa Britt Tikva; Varvara Maksimtšuk; Nayana Gaur; Riin Reimets; Allen Kaasik; Eero Vasar; Mario Plaas (Diabetology & Metabolic Syndrome)
Abstract Background and Aim Wolfram syndrome (WS) is a rare autosomal disorder caused by WFS1 gene mutations, currently lacking approved treatments. Preclinical and clinical reports suggest that diabetes medications, such as glucagon-like peptide-1 receptor agonist (GLP1-RA), slow WS-related diabetes and neurodegeneration, improving patient outcomes. Gamma-aminobutyric acid (GABA) has crucial role in pancreatic islet function and blood glucose regulation. However, its specific role in WS diabetic pathophysiology has never been explored. The aim of this study was to enhance the therapeutic efficacy of liraglutide in mitigating the progression of diabetes associated with WS through supplementation with GABA. Methods In this study, 5-month-old glucose intolerant WS rats and their wild-type littermates where daily treated with GABA (1 g/kg/day), liraglutide (0.4 mg/kg/day), or a combination of both. During the four-month experimental period, the diabetic phenotype was closely monitored using intraperitoneal glucose tolerance tests (IPGTT) and corresponding hormone measurements via enzyme-linked immunoassay. Following the treatments, immunohistochemical staining was performed to examine the morphology, cellular distribution, and health of Langerhans islets. Results Unlike in conventional diabetes models, GABA monotherapy alone had no significant effect on the diabetic phenotype in WS rats. In contrast, liraglutide monotherapy effectively delayed diabetes progression. Remarkably, the combined therapy of GABA and liraglutide reversed the diabetic phenotype, significantly enhancing glucose homeostasis, as well as insulin and C-peptide secretion. The combined treatment also increased β-cell mass and corrected the pancreatic Langerhans intra-islet ratio of α-, β-, and δ-cells. As a result, the overall morphology and cytoarchitecture of the pancreatic islets were fully restored, suggesting a potential role for these agents in preserving islet integrity. Additionally, both liraglutide and combination therapy increased the number of GAD (glutamic acid decarboxylase) 65/67-positive β-cells in WS rats, indicating an improvement in general β-cell health. Conclusion GABA monotherapy had no significant effect on the diabetic phenotype in WS rats, while liraglutide monotherapy effectively delayed diabetes progression. However, the combination therapy of GABA and liraglutide demonstrated a markedly superior effect, not only reversing the diabetic phenotype but also significantly enhancing glucose homeostasis, insulin and C-peptide secretion, and β-cell mass. This combined treatment led to a restoration of Langerhans islet architecture, correction of the endocrine cell proportions, and a notable increase in GAD65/67-positive β-cells, indicating improved β-cell health and function. These findings provide strong evidence supporting the evaluation of GABA and GLP-1 RAs as a combination therapy in clinical trials. Their synergistic effects may offer enhanced β-cell protection, promote functional recovery, and uncover novel therapeutic pathways for treating patients with WS. Graphical Abstract